Form, Meaning and Function of Argot in French Rap Song: Sociolinguistics Study - Aisyah Nadila Andree; Nany Ismail; Nani Darmayanti (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
Music is one of the way to express emotions, opinions, and also criticism. The lyrics helps us to communicate, and spread its story. Argot in rap song is a sociolinguistic phenomenon that spreads in all languages, including French. The author conducted this study with the aim of knowing the formation of argot used, the meaning behind, and what correlation it has with situation in Marseille. The writer uses descriptive analysis method and theories that support this research are the theory of sociolinguistics and the process of forming argot Calvet (1994), as well as the theory of meaning Baylon and Mignot (1995). The conclusion contains apocope, apheresis, suffixation, and metonymy. The most uses type of formation is metonym. Metonym can deliver a figurative meaning to achieve dramatic effect, but still maintain its secretive nature. Argot has a relation with how singer express their situation and condition within their lyrics.